Un élément du style oralisé dans la littérature médiévale. Le tempo du dialogue dans La Vie des Pères - Corinne Denoyelle (Perspectives Médiévales)
This article proposes a tool for the stylistic analysis of characters’ words. Observing the tempo, i.e. the speed of the dialogues gives the size and number of lines in a dialogue. Calculated this, way the tempo of the dialogue makes it possible to compare the texts and to perceive how the dialogues are part of a narrative project which, according to the authors, seeks to represent the liveliness of spontaneous speech or the monumentality of ornate speech. This observation helps highlight recurring procedures that demonstrate writing skills in addition to the study of tempo there is an analysis of the internal procedures of the line, which, by playing with ellipses, redundancies or dislocations, aim to create the effects of a orality. This methodology is applied to the collection of tales La Vie des Pères.